2009
DOI: 10.1016/j.ijnonlinmec.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Complex surface rays associated with inhomogeneous skimming and Rayleigh waves

Abstract: The Rayleigh wave, that propagates at the free surface of semi-infinite anisotropic medium, is composed of three inhomogeneous partial waves, each propagating along the surface with a different attenuation along the depth. Since this wave does not exhibit an attenuation on the surface, let us call it the homogeneous Rayleigh wave. The associated slowness corresponds to the real solution of the Rayleigh dispersion equation. Besides this classical solution, an infinite number of complex solutions of the Rayleigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…One question already raised relates to the maximum number of outgoing SAW there can be for any given surface. From the degree of the secular polynomial function 47 it would appear that for a generally anisotropic solid there is an upper limit of 27, but this encompasses unphysical and other types of solutions as well, and so the true upper limit for the number of SAW must be considerably lower than this, and lower still where there is symmetry. Another question is as follows: When s x passes through a critical value where an incoming and outgoing solution on R merge, guided by the analogous situation for bulk waves, one might anticipate that beyond that point there should be a pair of complex conjugate solutions corresponding to Rayleigh waves which are exponentially growing and decreasing along the surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One question already raised relates to the maximum number of outgoing SAW there can be for any given surface. From the degree of the secular polynomial function 47 it would appear that for a generally anisotropic solid there is an upper limit of 27, but this encompasses unphysical and other types of solutions as well, and so the true upper limit for the number of SAW must be considerably lower than this, and lower still where there is symmetry. Another question is as follows: When s x passes through a critical value where an incoming and outgoing solution on R merge, guided by the analogous situation for bulk waves, one might anticipate that beyond that point there should be a pair of complex conjugate solutions corresponding to Rayleigh waves which are exponentially growing and decreasing along the surface.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Ref. 47, which includes a discussion of inhomogeneous Rayleigh waves, may be a useful starting point for dealing with this question. Another intriguing question revolves around the occurrence of configurations where, in conformity with Snell's law, an incident Rayleigh wave is reflected as a Rayleigh wave at a point where it degenerates with the bulk wave continuum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, the faster being the skimming longitudinal wave (marked L) and the slowest being the Rayleigh surface wave (marked R). 31 From the Rayleigh pulse half temporal period τ (see Fig. 5), the central frequency of the Rayleigh wave is calculated at f R = 1/2τ = 1.7 GHz.…”
Section: A Saws Probed By Deflectometrymentioning
confidence: 99%
“…Recently, Deschamps and his collaborators [49][50][51] showed that the cuspidal triangles of the qS wave extend beyond the edges or vertices of the cuspidal triangles, and that this phenomenon can be explained by inhomogeneous plane waves. In order to show this, we perform a simulation using a two-dimensional qP-qS modeling algorithm based on the staggered Fourier method to compute the spatial derivatives [52].…”
Section: Numerical Simulationsmentioning
confidence: 99%